Uncovering Hidden Impacts of Disclosure through Interpretative Phenomenological Analysis - Timothy, Duesbury; Su Hie, Ting (Asian Scholars Network (ASNet), 2025)
Sharing personal information is a common aspect of communication and may reveal thoughts or feelings that have not been previously expressed or acknowledged. Such revelations can hold personal importance for the individual who shares them, making the reactions they perceive—whether verbal or nonverbal—emotionally significant. These perceived responses may leave lasting effects on the discloser, which can be identified through careful analysis. This study explored the hidden impacts of personal disclosure using Interpretative Phenomenological Analysis (IPA). An interview with one participant was recorded, transcribed, and examined through the IPA framework. At a surface level, the participant recounted feeling unsupported and isolated when her child was hospitalised. Deeper interpretation suggested that she possessed strong coping abilities that were recognised by her husband, leading to feelings of validation. Themes of anger also surfaced, reflecting her sense of vulnerability during that difficult time. The findings demonstrate how IPA can uncover underlying emotional meanings and subtle psychological impacts embedded within personal disclosures.